Emergency preparedness and response in palm oil mill and investigation of the employees' emergency preparedness knowledge and attitude - Ahmad Naim, Nabilah Aliyah; Omar, Rozita; Nik Ibrahim, Nik Nor Liyana (American Institute of Chemical Engineers, 2022)
Several legislations and standards have listed emergency preparedness and response (EPR) in palm oil mills as one of the requirements. EPR effectiveness depends on the knowledge and attitude of an individual. This study evaluated the EPR in a palm oil mill (POM) company and investigated the employees' emergency preparedness (EP), knowledge, and attitude. The potential emergency occurrences were identified through hazard identification, risk assessment, and risk control (HIRARC). Meanwhile, the current EPR practices were assessed through the Occupational Safety and Health Management System (OSHMS) emergency management checklist and the EP exercises. A social survey provided the data on the EP knowledge and attitude among the employees. There were two high-risk level work activities: welding and conveyor maintenance, rated at 12 and 16, respectively. The mill did not provide three elements of the 10 minimum requirements listed in the OSHMS guidelines. The EP exercises were successfully conducted. 63.5% of the respondents scored a moderate level of EP knowledge. A positive attitude toward EPR was found. There was no significant relationship between EP knowledge and attitude. The EPR practices in this POM company need improvement and enhancement, including the EP knowledge and attitude among the employees.